Process for preparing particles comprising poly(arylene(ether)sulfone)
Patent Information
- Application Number
- CN202280025476.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-01
- Filing Date
- 2022-03-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-03-25
Smart Images

Figure FT_1 
Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] This application relates to a method for preparing particles containing polyaryl(ether) sulfone, said polyaryl(ether) sulfone particles and their uses, products that can be prepared from particles containing polyaryl(ether) sulfone, and a method for recycling products prepared from particles containing polyaryl(ether) sulfone. Background Technology
[0002] Polyaryl(ether) sulfone polymers are high-performance thermoplastics characterized by high heat resistance, good mechanical properties, and inherent flame retardancy. Therefore, they can be used in a wide variety of applications. Methods for preparing them from aromatic dihalogen compounds and aromatic bisphenols or their salts, with or without solvent, are known. Polyaryl(ether) sulfones are biocompatible and are therefore also used as materials for molded articles in the household and food industries, as well as for film-forming applications in various industrial and medical fields.
[0003] EP 548 683 A1 and EP 548 684 A1 disclose the agglomeration of polyphenylene ether powder, particularly poly-2,6-dimethyl-1,4-phenylene ether, in a tablet press or a compactor consisting of two counter-rotating rollers and a screw-based machine, at a pressure corresponding to a linear force of 1 to 100 kN / cm and a temperature of 10 to 150°C. EP 640 640 A1 describes the agglomeration of polyphenylene ether flakes, particularly semi-crystalline polyarylene ethers, preferably polyarylene ether ketones, at a temperature of 250 to 320°C. EP 3 573 800 B1 discloses further agglomeration of expanded sulfone polymers.
[0004] In many applications, high-purity polyarylene (ether) sulfones are desired. Therefore, the problem addressed in this paper is to discover a method for preparing high-purity or even very high-purity polyarylene (ether) sulfones. One aspect is to discover a method that improves reliability at high throughput. Furthermore, there is a need to support the easy manufacture of high-purity polyarylene (ether) sulfones in the form of articles such as fibers, moldings, or membranes. A particular motivation is to provide polyarylene (ether) sulfones for the manufacture of thin-walled articles, especially feeding bottles or filaments for membranes. Specifically, polyarylene (ether) sulfones with uniform processability are sought. Summary of the Invention
[0005] A method for preparing particles comprising polyaryl(ether) sulfone has been discovered, and the method comprises agglomerating a fine particulate material comprising polyaryl(ether) sulfone, wherein... (i) The moisture content of the educt (starting material) is not greater than 2% by weight, based on the total weight of the educt and determined according to the moisture that escapes from the educt when heated to 160°C; (ii) The moisture content of the ambient air introduced from the outside into the device for agglomeration is 40% to 80%, as measured by using a hygrometer, and (iii) The temperature of the ambient air is 15 to 35°C, and is measured when the ambient air is introduced into the device.
[0006] In addition, we also found particles containing polyarylene (ether) sulfone, wherein the C of the particles Values below 15, and where C The value was determined by CieLab Spin measurement, and at least 60% by weight of the particles were of particle size (d). 50 The values ranged from 2 mm to 3.5 mm, determined by dynamic image analysis. Attached Figure Description
[0007] Figure 1 The metering time of product particles during injection molding is shown compared to flakes and granules, wherein Example A2 uses product particles agglomerated by the methods disclosed herein, Comparative Example VA2 uses PESU in flake form, and Comparative Example VA3 uses PESU in granule form. Detailed Implementation
[0008] The term "product particles" is also used below for particles containing polyaryl(ether) sulfone. The term "separate" is also used below for fine particulate materials containing polyaryl(ether) sulfone.
[0009] The polyaryl(ether) sulfone can be a single polyaryl(ether) sulfone or a mixture of multiple polyaryl(ether) sulfones (e.g., two or more). The polyaryl(ether) sulfone is preferably amorphous. In the case of a mixture of multiple polyaryl(ether) sulfones, at least one is preferably amorphous. In the above mixtures, it is preferred that the proportion of amorphous polyaryl(ether) sulfone is greater than 50% by weight, particularly greater than 90% by weight, based on the mixture. Of the mixtures, those consisting only of multiple amorphous polyaryl(ether) sulfones are particularly preferred.
[0010] Those skilled in the art will understand that any polymer that can be a homopolymer or copolymer in nature is typically a mixture of individual polymers that differ structurally in their chain length, degree of branching, or end-group properties. Therefore, the use of mixtures as described above implies the inclusion of different types of polymers, each of which may have the structural differences described above.
[0011] Preferably, an amorphous polyarylene (ether) sulfone is used in the method of the present invention.
[0012] The polyarylene (ether) sulfones particularly suitable for the methods of the present invention are amorphous, i.e., neither crystalline nor semi-crystalline. Methods for determining the crystallinity of polymers are well known to those skilled in the art. They are typically determined by DSC measurements. In the case of amorphous polyarylene (ether) sulfones, no melting point can be detected by DSC measurements. The glass transition temperature (Tg) of amorphous polyarylene (ether) sulfones or two or more Tg values of mixtures of polyarylene (ether) sulfones can be from 130 to 240 °C. Typically, the Tg of amorphous polyarylene (ether) sulfones or mixtures of two or more polyarylene (ether) sulfones with melt viscosities up to 1200 Pas, or the highest Tg of each, is from 130 to 200 °C, preferably from 160 to 200 °C. The Tg of amorphous polyarylene (ether) sulfones or mixtures of two or more polyarylene (ether) sulfones with higher viscosity, or the highest Tg of each, is 200 to 240°C, preferably 210 to 240°C. Methods for determining Tg are described in the examples.
[0013] The structure of the preferred amorphous polyarylene (ether) sulfone, as described above, is as follows.
[0014] Polyaryl(ether) sulfones can be homopolymers or copolymers. Copolymers can be random copolymers or block copolymers. Polyaryl(ether) sulfones typically contain -O- and -SO2- groups linking aryl groups. It may also contain other groups linking aryl groups, provided that the polyaryl(ether) sulfone remains amorphous and does not become crystalline or semi-crystalline. Preferably, polyaryl(ether) sulfones contain only -O- and -SO2- groups linking aryl groups. Preferably, the aryl group is phenylene or biphenylene. The aryl group may be unsubstituent or may have one or more substituents, such as sulfonic acid groups. In addition to aryl groups, polyaryl(ether) sulfones may also contain non-aromatic groups or blocks, preferably phenylene or biphenylene. Examples of blocks are blocks derived from one or more alkylene ethers, such as ethylene oxide and / or propylene oxide. Non-aromatic groups include, for example, those derived from invert sugars, such as isosorbide. Preferred polyaryl(ether) sulfones are polyphenylene sulfone (PPSU), polysulfone (PSU), and / or polyether sulfone (PESU); PPSU, PSU, or PESU homopolymers are particularly preferred herein. For many applications, especially for the preparation of thin-walled products, PPSU homopolymers are preferred.
[0015] Polyaryl(ether) sulfones may have—depending on their preparation method—terminus such as hydroxyl, halogen, amino, epoxy, or anhydride end groups, for example, anhydride end groups derived from phthalic anhydride or 4-chloro-1,8-naphthalenedicarboxylic anhydride. Polyaryl(ether) sulfones may also have end groups obtained by capping reactive end groups with a capping agent, which may be a monofunctional compound, such as methyl chloride. Among the end groups, hydroxyl, chlorine, and / or methoxy are preferred. PPSU, PSU, or PESU, particularly PPSU, PSU, or PESU homopolymers, and, as described for many applications, PPSU homopolymers preferably containing one or more of the aforementioned end groups such as hydroxyl and chlorine or chlorine and methoxy end groups, are advantageously used in the methods disclosed herein.
[0016] In the context of this disclosure, the abbreviations PPSU, PESU, and PSU conform to DIN EN ISO 1043-1 (Plastics - Symbols and abbreviated terms - Part 1: Basic polymers and their special characteristics (ISO 1043-1:2001); German version EN ISO 1043-1:2002).
[0017] The weight-average molar mass Mw of polyarylene (ether) sulfone is preferably from 10,000 to 150,000 g / mol, particularly from 15,000 to 120,000 g / mol, more preferably from 18,000 to 100,000 g / mol, and is determined by gel permeation chromatography in dimethylacetamide solvent using narrowly distributed polymethyl methacrylate as a standard.
[0018] In addition, polyarylene sulfone at 350℃ / 1150 s -1 The apparent melt viscosity is preferably from 20 to 1200 Pas, more preferably from 50 to 700 Pas. Methods for determining the apparent melt viscosity are described in the examples. Apparent melt viscosity can be used to evaluate flowability.
[0019] The above-mentioned preferred method for preparing amorphous polyarylene (ether) sulfones is known to those skilled in the art and is described, for example, in Herman F. Mark, "Encyclopedia of Polymer Science and Technology", 3rd edition, Vol. 4, 2003, "Polysulfones", pages 2 to 8, and in Handbook of Polymer Synthesis, 2nd edition, 2005, pages 427 to 443, Hans R. Kricheldorf, "Aromatic Polyethers".
[0020] The precipitate is a fine particulate material containing polyarylene (ether) sulfone.
[0021] In most applications, the preferred precipitate comprises amorphous polyarylene (ether) sulfone, preferably polyphenylene (ether) sulfone (PPSU), polysulfone (PSU) or polyether sulfone (PESU), wherein PPSU, PSU or PESU homopolymers are generally preferred, or PPSU homopolymers as described above for many applications.
[0022] The segregated material can be in the form of powder or any other fine particulate material (e.g., flakes or flakes containing powder). The particle size and particle size distribution of the segregated material can vary over a wide range. For example, particle size d can be used. 50 Separates in the form of particles with a particle size of 0.2 to 5 mm, preferably 0.5 to 4 mm. Particle size d 50 Separates in the form of particles with sizes from 1 mm to 3 mm are particularly suitable for the methods of the present invention because they produce a highly uniform delivery, thereby minimizing variations during agglomeration. Methods for determining the particle size of the separates are described in the examples.
[0023] The fine particulate material may contain one or more additives and polyarylene (ether) sulfone (and typically small amounts of residual material from its preparation). If the fine particulate material contains one or more additives, the proportion of these additives is typically no more than 10% by weight, based on the total weight of the fine particulate material. In each case, based on the total weight of the exfoliated material, the fine particulate material typically contains 0 to 7% by weight, preferably 0 to 5% by weight, of one or more additives and 93 to 100% by weight, preferably 95 to 100% by weight, of polyarylene (ether) sulfone, wherein PPSU, PSU, and PESU are typically preferred, with the corresponding homopolymers, or for many applications, PPSU homopolymers are typically particularly preferred.
[0024] One or more additives in the segregate may be solid or liquid, or liquid at the temperature at which agglomeration occurs. Particularly for the preparation of transparent products, such as films, foils, or moldings, such as thin-walled transparent moldings, it is generally advantageous to disperse one or more additives very well in the segregate or in the product particles prepared therefrom. For this purpose, one or more additives are advantageously fine-grained or liquid, and preferably liquid or micronized. When additives are to be added to the segregate, they can be added as is or in the form of a masterbatch. Examples of materials that can be used as additives include coloring agents (e.g., pigments), stabilizers, release agents, flow aids, foaming agents, and lubricants. Particularly for the use of product particles obtained by the methods disclosed herein that require a blow molding step, it is preferable that the segregate contains stearic acid.
[0025] If the purpose is to prepare product particles that can be further processed to obtain transparent products, particularly transparent films, foils, or molded articles, then the fine particulate material is additive-free, i.e., the precipitate consists of polyarylene (ether) sulfone. Alternatively, the precipitate contains one or more additives (particularly stearic acid) that are uniformly dispersed to such an extent that one or more additives do not fog in the product prepared from the product particles.
[0026] In the case of preparing high-purity product particles for further processing to obtain products where purity is particularly important, it is most preferable that the precipitate is free of additives. In this case, it is also preferable that the purity grade of the precipitate is 1 or 2, particularly purity grade 1. The purity grade can be determined by optical evaluation using filter testing. The methods that can be used are illustrated in the examples.
[0027] Aggregation of the separated products is carried out within the operating range defined by the following: (i) Moisture content of the separated material, (ii) Moisture content of ambient air, and (iii) The temperature of the ambient air.
[0028] Within the operating range, the tendency of the segregated material to clump can be reduced or completely eliminated.
[0029] The precipitate can be used in a dried or partially dried form. Although the moisture content in the precipitate may be below the detection threshold, a certain amount of moisture in the precipitate can usually be detected. The moisture content of the precipitate is typically at least 0.02% by weight, based on the total weight of the precipitate. The moisture content can be residual moisture from the preparation process of polyarylene (ether) sulfone. However, it can also be moisture from the storage conditions of polyarylene (ether) sulfone, or both. The moisture content can be water and / or solvents, such as those used in the preparation of polyarylene (ether) sulfone. It is generally preferred that the precipitate contains no more than 2% by weight of moisture, particularly no more than 1% by weight, based on the total weight of the precipitate. Methods for determining the moisture content of the precipitate are described in the examples.
[0030] Ambient air is air introduced into the device from the outside. This can be, for example, indoor air, and is introduced in the method by pressure or suction; suction is generally preferred herein. It is particularly advantageous that the ambient air introduced into the device, especially by suction, has been purified. Methods and apparatus for this purpose are known to those skilled in the art. For example, the ambient air can be filtered. Filters such as candle filters are suitable for this purpose. The filter fineness can be fine or very fine, but the cost of devices with filter fineness values substantially less than 1 μm generally excludes the industrial-scale use of such filters. Good purification of ambient air can generally be achieved with filters having a filter fineness value of 20 µm or less. Filters with a filter fineness value of 10 µm or less, for example, 1 to 5 µm, are preferred.
[0031] When the moisture content of the precipitate is not greater than 2% by weight based on the total weight of the precipitate, the moisture content of the ambient air can be 40% to 80% at an ambient air temperature of 15°C to 35°C. When the moisture content of the precipitate is 0.2% to 0.5% by weight based on the total weight of the precipitate, aggregation is preferably carried out at lower temperatures and lower ambient air moisture contents. Therefore, advantageous conditions are an ambient air temperature of 15°C to 25°C and an ambient air moisture content of 40% to 70%, particularly an ambient air temperature of 15°C to 25°C and an ambient air moisture content of 40% to 60%. The moisture content of the precipitate can be determined by the method described in the examples. The ambient air temperature and its moisture content can be determined by the method described in the examples.
[0032] The advantages of the methods disclosed herein are that they produce non-caking product particles. Corrosion can also be reduced or eliminated. The methods can be carried out reliably even at high throughput.
[0033] The segregates are agglomerated by the method of the present invention. For agglomeration and / or during the agglomeration process, the segregates are heated, typically initially at a preferred ambient temperature. The material temperature during agglomeration is 180 to 240°C. Preferably, the material temperature during agglomeration is 210 to 240°C. Amorphous polyarylene (ether) sulfones having terminal hydroxyl groups or substituents on arylene groups or having non-aromatic groups or blocks are generally preferred to agglomerate at a material temperature just above 180°C, for example, 190 to 220°C. The material temperature described herein can be determined by the method described in the examples. If the material temperature is below 180°C, an increase in viscosity occurs, making agglomeration more difficult or impossible. If the material temperature is above 240°C, the material will clump. A dark-colored product may also be obtained. Furthermore, the product may have a high proportion of fine particles and / or a relatively high proportion of non-uniform, sharp-edged particles. This can adversely affect the free-flow properties for subsequent further processing and / or may require appropriate separation or return steps.
[0034] Agglomeration typically takes place in an apparatus containing at least one agglomeration tool that moves the separated material therein. An agglomeration apparatus usually includes one agglomeration tool. Agglomeration can also take place in more than one apparatus, which can operate simultaneously or—particularly in batch operations—operate at different times. This allows, for example, agglomeration to occur in one apparatus while another apparatus is kept, for example, clean. Furthermore, after all the separated materials have been fed into one apparatus, additional separated materials can be fed into another apparatus while the process in the first apparatus continues. However, separated materials can also be added to all apparatuses simultaneously, and agglomeration can also occur simultaneously within the apparatuses.
[0035] The methods disclosed herein can be performed using equipment made of conventional chemical materials such as stainless steel, duplex steel, titanium, Hastelloy, or hard metals. In the above context, depending on the intended use of the equipment, and as will be understood by those skilled in the art, a portion of the equipment may be made of a material different from that of other portions of the equipment.
[0036] The temperature of the apparatus used for agglomeration allows the material temperature to be reached during the agglomeration process. The temperature of the apparatus for agglomeration depends particularly on the expected duration of agglomeration and / or the properties of the polyarylene (ether) sulfone contained in the precipitate. Frictional heat generated by the apparatus during agglomeration can also contribute to reaching the material temperature. The temperature of the agglomeration tool in contact with the material during agglomeration is typically preferably 200 to 240°C.
[0037] Apparatus for agglomerating thermoplastics is known in itself. In the method of the invention, a flatbed compactor can be used, for example, in which the segregated material is moved outward between two plates (e.g., as shown in DE 1 454873 or DE 1 454 875). Apparatus comprising at least one agglomeration tool, such as a hollow chamber having elements rotating therein, can also be used. The segregated material can be agglomerated, for example, in an agglomeration chamber, where it is moved by rotating compressor blades and discharged through a perforated die (e.g., disclosed in EP 373 372). Apparatus that can also be mentioned by way of example and used in the method of the invention is, for example, a compression chamber known from DE 10 2005 018 733. Apparatus for agglomeration generally includes means suitable for crushing the discharged material, such as blades, laser beams, or water jets.
[0038] For reliability and increased throughput, it is preferable to convey the segregated material to the agglomeration tool via a conveying screw with a thread depth of at least 5 mm at a throughput of 250 kg / h. The thread depth at a throughput of 250 kg / h is typically up to 15 mm. Conveying screws with smaller or larger thread depths can be used at this throughput; however, even when using particle sizes (d... 50 When the segregation is 1 to 3 mm, it can also lead to irregular conveying and a lack of uniformity in product particle size. A conveying screw with a thread depth of 8 to 12 mm (flux of 250 kg / h) is advantageous because it contributes to uniform conveying and better uniformity of product particle size. Based on the above, those skilled in the art can select a conveying screw with a suitable thread depth for smaller or larger flow rates. Preferably, the conveying screw is designed for processing large volumes of flowable solids and / or flowable solids with low bulk density. Among the aforementioned screws, a thread depth of 8 to 12 mm (flux of 250 kg / h) is generally preferred, and it is designed for conveying densities of 100 to 350 kg / m³. 3 A conveying screw for transporting flowable solids. A conveying screw with a thread depth of 8 to 12 mm (throughput 250 kg / h) is particularly preferred, designed for conveying densities of 150 to 300 kg / m³. 3 A flowable solid.
[0039] The methods disclosed herein may include compacting and homogenizing product particles in one or more other devices, the product particles being obtained by agglomerating segregates in one or more devices containing agglomeration tools. For this purpose, the product particles obtained from the agglomeration tools may then be conveyed, for example, to a thermal granulator, where they may be processed into granulates. This is generally not preferred. Preferably, after removing the product particles from the agglomeration device, they are cooled and ready for use without further compaction or homogenization. Furthermore, the methods disclosed herein may include one or more other devices. If necessary, the methods may include, for example, one or more devices that can separate product particles from dust particles. An example of this type of separator is a sieve. This type of separator is generally preferred not to be used.
[0040] In the method of this invention, the precipitates agglomerate to form product particles. Therefore, in terms of their chemical composition, the product particles consist of the precipitates. If there is any deviation between the composition of the product particles and the composition of the precipitates, the minimal material introduction due to the method technique will only result in a very small deviation. Therefore, for a description of the chemical composition of the product particles, please refer to the description of the precipitates.
[0041] The product particles are light or very light colored to essentially colorless or completely colorless.
[0042] The color of the product particles is measured by the chromaticity value C. For non-colored materials, C The value is zero. The C of the product particles. Values below 15 were determined by CieLab Spin-measurement. Polyaryl(ether) sulfone particles containing higher glass transition temperatures (Tg) generally exhibit a greater tendency to color than particles with lower Tg. Polyaryl(ether) sulfone particles containing glass transition temperatures or mixtures of various polyaryl(ether) sulfones with a maximum Tg of 200°C to 240°C have a C value below 15. The values are typically in the range of 15 to slightly or slightly below 15, determined by CieLab Spin measurements. For example, a typical value can be 12 to 15. Polyaryl(ether) sulfone product particles containing glass transition temperatures or mixtures of various polyaryl(ether) sulfones with a maximum Tg of 130°C to 200°C, have a C... Values are often less than or much less than 15, determined by CieLab's Spin-measurement method. For example, typical values can be between 8 and 12. This can be used to determine C. The method for determining the value is described in the examples.
[0043] The average particle size of the product particles is larger than the particle size of the segregated material. The particle size d of more than 60% by weight of the product particles is larger than 60% by weight. 50The value is 2 mm to 3.5 mm, preferably 2.5 mm to 3.5 mm, and particularly preferably 3 mm to 3.5 mm. It can be used to determine d by dynamic image analysis. 50 The method for determining the value is explained in the examples.
[0044] Furthermore, the bulk density of the product particles is greater than that of the segregated material. The bulk density of the product particles is typically 400 to 600 kg / m³. 3 Methods for determining bulk density are illustrated in the examples. Product particles with this bulk density exhibit good storage, conveying, and transport properties.
[0045] Product particles are typically spherical, elliptical, and to some extent oval. Product particles can be characterized by the Hausner coefficient. The Hausner coefficient of the product particles is preferably from 1.05 to 1.3, particularly from 1.05 to 1.2, and especially preferably from 1.05 to 1.18. The Hausner coefficient can be measured as described in the examples. Product particles also preferably have a sphericity of 0.6 to 1.0, more preferably 0.7 to 1.0, and even more preferably 0.8 to 1.0. Methods for measuring sphericity are described in the examples. Particles also preferably have a Feret diameter of 0.6 to 1.0, more preferably 0.7 to 1.0, and even more preferably 0.8 to 1.0. Therefore, product particles having the combination of the above-described Hausner coefficient, sphericity, and Feret diameter are generally preferred. The product particles exhibit friction between a bulk solid and a surface, as well as internal friction, making them suitable for molding methods such as injection molding, blow molding, or injection stretch blow molding. The product particles are particularly suitable for blow molding and injection stretch blow molding. In particular, thin-walled molded articles can often be advantageously produced from product particles by blow molding or stretch blow molding.
[0046] The SO2 content of the product particles is preferably less than 40 mg / kg. This is advantageous because it minimizes damage to equipment due to corrosion during the processing of the product particles. Methods for determining the SO2 content are illustrated in the examples.
[0047] In particular, when the precipitate with a purity grade of 1 or 2, especially a purity grade of 1, is used in the method, high-purity product particles can be obtained by the method of the present invention. The purity grade can be determined as described in the examples. The high-purity product particles are preferably free of additives. The high-purity product particles are suitable for, for example, the preparation of foils or films, foams or molded articles in the food industry. In particular, the high-purity product particles are suitable for the preparation of thin-walled molded articles, wherein those are preferably intended to be sterilizable and / or highly transparent.
[0048] To further process the product particles, such as in injection molding, extrusion, and blow molding processes, it is advantageous to minimize the residual moisture content. The residual moisture content is typically only water retained from the segregated material, but a small amount of residual solvent may be present. For the purposes of the above, it is generally preferred that the residual moisture content of the product particles be less than 0.5% by weight, particularly less than 0.1% by weight, based on the total weight of the product particles. Although the residual moisture content of the product particles may be below a detection threshold, it is generally detectable. The residual moisture content is typically 0.1% by weight or more, for example, from 0.15% to 0.5% by weight, in each case based on the total weight of the product particles. Methods for determining the moisture content of the product particles are illustrated in the examples.
[0049] The product granules disclosed herein can be processed using standard processing machinery for granule processing, and in particular, since they have essentially the same injection weight as the granules, the feed time and throughput essentially correspond to the feed time and throughput of the granules.
[0050] The product particles disclosed herein can be used to prepare coatings, films, foams, foils, membranes, or moldings. In particular, the particles are suitable for applications where transparency, high purity, and / or light inherent color are important. Furthermore, the particles are advantageously suited for applications with thin or very thin walls. A particular problem arising in the preparation of thin-walled or very thin-walled moldings is the tendency of the injection molding material used to gel. When the product particles are used in the preparation of such moldings, surface defects such as gelation can generally be reduced or eliminated.
[0051] Coatings, films or foams, foils or membranes, or molding articles are also disclosed, wherein these are prepared using product particles. Molding articles may be, for example, thin-walled or very thin-walled molding articles. Very thin-walled molding articles may be, for example, hollow fibers. Related molding articles are typically those comprising one or more walls with a wall thickness of less than 2 mm, covering at least 50% of their surface area based on the total surface area of the molding article. For many applications, preferred molding articles are those comprising one or more walls with a wall thickness of 0.3 to 1.7 mm, particularly 0.5 to 1.5 mm, covering at least 50% of their surface area based on the total surface area of the molding article. The range of wall thickness variation is generally small herein. Methods for determining the wall thickness are illustrated in the examples.
[0052] Foams, foils, or moldings prepared using product granules can be recycled under the conditions described above for preparing product granules. Therefore, a method for recycling foams, foils, films, or moldings is also disclosed, and the method includes preparing pulverized material and agglomerating it to obtain recyclable granules. This method is advantageous for recycling, particularly when the material to be recycled is of a single type. It is particularly preferred to use edge trimmings derived from methods for preparing coatings, foams, foils, films, or moldings that are prepared using granules. Therefore, a method for recycling said edge trimmings is also disclosed, comprising preparing pulverized material and agglomerating it to obtain recyclable granules.
[0053] The methods disclosed herein can be used to prepare product particles that are highly suitable for preparing transparent or highly transparent films, foils or molded products, especially because additives (such as stearic acid) can usually be incorporated more successfully and uniformly compared to a secondary mixing step.
[0054] Furthermore, the method disclosed herein can produce particles with low SO2 content, and can have an even lower SO2 content compared to particles containing the corresponding polyarylene (ether) sulfone. Although SO2 content typically decreases over time, particles exhibiting low SO2 content can be used without extending storage time. In particular, when the application involves metallization, surface defects can be avoided by using the particles with the low SO2 content.
[0055] Product particles prepared by the disclosed methods typically have uniform processing characteristics.
[0056] Example Determination methods Ambient air The moisture content at ambient temperature is measured using a hygrometer located one meter above the intake point of the ambient air.
[0057] The temperature of the ambient air was measured directly at the intake point of the ambient air using a thermometer (PT 100).
[0058] Apparent melt viscosity The apparent melt viscosity was determined using a capillary rheometer. The apparent viscosity was measured as a function of shear rate at 350°C in a Göttfert Rheograph 2003 capillary viscometer, with a circular capillary length of 30 mm, a radius of 0.5 mm, a die inlet angle of 180°, a melt storage container diameter of 12 mm, and a preheating time of 5 minutes. The recorded value was obtained at 1150 s. -1 The values that were measured.
[0059] Bulk density of particles The bulk density of the particles was determined according to DIN EN ISO 60 (January 2000).
[0060] C value A Data Color SF 600 spectrophotometer with an integrating sphere and d8 measurement geometry was used. Color measurements were performed relative to a white calibration standard using a SPIN (Specular Included) device on a test plaque (60x60x3mm injection-molded test sample). Color coordinates were calculated in the CieLab color matching system using a D65 beam pattern and a 10° standard observer, according to DIN 6174, 1979_01.
[0061] Glass transition temperature The material sample was heated from 20 °C to 350 °C at a heating rate of 20 K / min (first heating). After cooling the sample to room temperature, it was reheated to 350 °C at a heating rate of 20 K / min (second heating). The DSC trace of the amorphous polyarylene (ether) sulfone after the second heating showed only one glass transition (Tg), or, in the case of a mixture of different amorphous polyarylene (ether) sulfones, two or more glass transitions (Tg) were shown, but no melting endothermic reaction was observed.
[0062] Hausner ratio The Hausner ratio is calculated using tamped density ρ. 夯实 (According to DIN ISO 787-11 DE, October 1995) and bulk density ρ 未夯实 (Calculated according to DIN EN ISO 60 DE, January 2000) (2500 cycles in each case). The Hausner ratio characterizes not only the flowability and compressibility of bulk solids, but also the uniformity of particles in terms of size, shape, hardness, and most importantly, adhesion.
[0063] Material temperature during aggregation The material temperature was measured directly at the particle preparation location using an infrared thermometer (testo 830-T2).
[0064] Moisture content of segregates and products Moisture content was determined by evaporating the water from the sample and titrating the collected water. In this study, moisture content was determined using a Metrohm KF-852 Titrando apparatus. Approximately 0.1 g (accurate to 0.001 g) of sample was weighed on an analytical balance and placed into a 5 ml ampoule. The ampoule was sealed using sealing clamps. The ampoule was placed in an apparatus heated to 160°C, where the membrane was punctured and the ampoule was capped using a needle. The evaporated water was entrained into the titration cell by an air stream (gas flow rate 60 ml / min). Titration continued until no further water escaped from the ampoule. Data are expressed as a percentage by weight, based on the mass of the precipitate or product.
[0065] molar mass The weight-average molar mass (Mw) and number-average molar mass were determined by gel permeation chromatography relative to PMMA standards in DMAC as a solvent.
[0066] Particle size of the segregated material, as well as particle size, sphericity, and Fret diameter of the product particles. Particle size of the segregated material and particle size of the product (d) 50 The values, sphericity, and Fretter diameter were determined in free-fall measurements using dynamic digital image processing according to ISO 13322-2 (2006). The apparatus used in this paper for determining these variables was a Camsizer XT. These variables were determined by utilizing the maximum chord length of the particle projection. Maximum chord length x c This refers to the longest dimension of the particle's projection perpendicular to the measurement direction. Minimum chord length x cmin It is the shortest of all maximum chord lengths measured from all measurement directions of the particle projection. cmin The software used for the measuring apparatus employed in this paper provides a basic fit. In this paper, the Feret diameter is represented by the ratio xFeretmin / xFeretmax. Sphericity is a measure of particle roundness. A value of 1 corresponds to an ideal sphere. Sphericity can be calculated using the measured perimeter U and the measured area A of the particle's projection: Purity grade of the separated product Under nitrogen atmosphere and with stirring, 20 g of the test material was dissolved in 100 ml of filtered, sodium hydroxide-free N-methyl-2-pyrrolidone at 100 °C. The solution was pumped through a paper filter (black band filter, e.g., MN 640w, Ø 70 mm) using a water pump. The size of visible dirt spots on the paper filter was then visually determined using a template. The number of dirt spots was determined by counting, and they were classified according to their size in this paper. The following formula was used to determine the area of the dirt spots for comparison: Dirt [mm] 2] / 20 g = ∑ (number of spots x size according to size grade [mm]) 2 ]) / 20 g Based on the test results, the purity of the materials is divided into three categories: Sulfur dioxide content of particles The SO2 content of the particles was determined by headspace GC / MS of chloroform solution.
[0067] viscosity Viscosity was determined according to ISO 307, 1157, 1628, 2019 in 0.01 g / ml phenol / 1,2-dichlorobenzene (1 / 1).
[0068] Wall thickness The wall thickness was determined according to DIN EN ISO 16810 2014-7-1.
[0069] PPSU for Invention Embodiments 1 and A1 and Comparative Embodiments V1 and VA1 Polyphenylene sulfone homopolymer (PPSU) was used. PPSU was completely amorphous, with a glass transition temperature (Tg) of 220 °C, a weight-average molar mass (Mw) of 45,500 g / mol, an Mw / Mn ratio of 2.7, and a viscosity of 71 cm⁻¹. 3 / g (Ultrason® P purchased from BASF).
[0070] PESU for Invention Embodiment A2 and Comparative Embodiment VA2 Poly(aryl ether sulfone) homopolymer (PESU) was used. PESU was completely amorphous, with a glass transition temperature (Tg) of 225 °C, a weight-average molar mass (Mw) of 48,000 g / mol, an Mw / Mn ratio of 2.7, and a viscosity of 56 cm⁻¹. 3 / g (Ultrason® E purchased from BASF).
[0071] Invention Embodiment 1 PPSU was used as the precipitate, and no additives were included. The precipitate had a moisture content of 0.05% by weight and d 50 The particle size is 2513 µm. The precipitate used is of purity grade 1 and contains no additives.
[0072] The segregated material is loaded into the feed container of the agglomeration unit via a pneumatic conveying system. A conveying screw (10 mm thread depth; 250 kg / h throughput) transports the segregated material from the feed container to the agglomeration tool. The agglomeration tool used is an agglomeration chamber, in which the segregated material moves by rotating compressor blades, exits through a perforating die, and is shredded by rotating blades (Pallmann Plastagglomerator PFV 250 / 20). The temperature of the perforating die is 235 to 245°C. The ambient air moisture content is 73%, and the ambient air temperature during agglomeration is 28 ± 2°C.
[0073] The obtained product particles have a particle size of 2881 µm (d). 50 (Value), bulk density is 490 kg / m³ 3 The Hausner coefficient is 1.02, the sphericity is 0.767, and the b / I3 value is 0.672. The glass transition temperature of PPSU remains constant at 223 °C. The value is 11.65. The purity level remains unchanged at level 1, and the residual moisture content is less than 0.02%.
[0074] Comparative Example V1 The precipitate used is as described in Embodiment 1 of the invention, and the only difference between it and the precipitate used in Embodiment 1 is its moisture content. The moisture content of the precipitate is 0.25%.
[0075] The agglomeration conditions differ from those used to prepare product particles only in that the temperature of the perforating die is 250 to 260°C, the moisture content of the ambient air is 87%, and the ambient air temperature is 19°C.
[0076] The particle size (d) of the obtained product particles 50 Its diameter is 3062 µm, its sphericity is 0.732, its Fret diameter is 0.656, and its bulk density is 467 kg / m³. 3 .
[0077] Invention Application Example A1 and Comparative Example VA1 Injection bowl (mold 3.5: dimensions: dtop = 280 mm, dbottom = 115 mm, h = 110 mm, wall thickness: 2.8 mm, central gate, cold runner, injection weight: 318 g) was molded using an injection molding machine (Krauss-Maffei KM300 / 1400-C2) with a locking force of 300 t and a screw diameter of 50 mm.
[0078] The PPSU homopolymer product particles obtained in Example 1 of the invention are used.
[0079] The comparison was made using granules made from PPSU as described in Embodiment 1 of the invention.
[0080] Particle size (d) of granules 50 Its diameter is 3282 µm, its sphericity is 0.943, its Fret diameter is 0.847, and its bulk density is 760 kg / m³. 3 C of granules The value is 23. • Baseline of average number of injections: 30 injections • Screw speed (m / s); Standard = 100 rpm = 0.29 m / s Application Example A2 of the Invention and Comparative Examples VA2 and VA3 Using an injection molding machine (Demag Systec 100 / 420-200) with a locking force of 100 t and a screw diameter of 25 mm, inject a T7 / 2 mm flow screw (exactly: T7.6.2) with a screw width of 10 mm, a thickness of 2 mm and an opening length of 46.5 g.
[0081] Embodiment A2 of the invention uses product particles agglomerated by the method disclosed herein. The product particles contain no additives. The bulk density is 483 kg / m³. 3 .
[0082] The particle size (d) of the obtained product particles 50 The sample has a diameter of 3080 µm, a Hausner coefficient of 1.13, a sphericity of 0.726, a Freyter diameter of 0.642, and a bulk density of 483 kg / m³. 3 .
[0083] Comparative Example VA2 uses a bulk density of 290 kg / m³ 3 PESU in thin sheet form.
[0084] Comparative Example VA3 uses PESU in granular form with a particle size (d) 50 The sphericity, Fret diameter, and bulk density substantially correspond to the pellets used in Comparative Example VA1.
[0085] Figure 1 This indicates that the metering time of the product particles shows significantly less variation compared to both flakes and granules, meaning that the product particles have more uniform processability.
Claims
1. A method for preparing particles comprising polyarylene ether sulfone, the method comprising agglomerating a fine particulate material comprising polyarylene ether sulfone, i.e., a segregate, wherein... (i) The moisture content of the segregated material is not greater than 2% by weight, based on the total weight of the segregated material and determined according to the moisture content released from the starting material heated to 160°C; (ii) The moisture content of the ambient air introduced from the outside into the device for agglomeration is 40% to 80%, as measured by using a hygrometer, and (iii) The ambient air temperature is between 15 and 35°C, measured when the ambient air is introduced into the device. The temperature of the area in contact with the material during the aggregation process of the aggregation tool is 200 to 240°C.
2. The method according to claim 1, wherein the moisture content of the segregated material is not greater than 1% by weight, based on the total weight of the segregated material and determined according to the moisture content that escapes from the segregated material heated to 160°C.
3. The method according to claim 1 or 2, wherein the segregated material is conveyed to an agglomeration tool for agglomeration by a conveying screw, the conveying screw having a thread depth of 5 to 15 mm at a throughput of 250 kg / h.
4. The method of claim 3, wherein the agglomeration tool is a hollow cylinder having elements therein that rotate.
5. The method according to claim 1 or 2, wherein the polyarylene ether sulfone is amorphous.
6. Particles comprising polyarylene ether sulfone prepared by the method according to any one of claims 1 to 5, wherein the Ci is measured according to CieLab spin. Values below 15, and at least 60% by weight of the particles having a particle size d 50 The values ranged from 2 mm to 3.5 mm, determined by dynamic image analysis.
7. The particles comprising polyarylene ether sulfone according to claim 6, wherein the polyarylene ether sulfone is polyphenylene ether sulfone.
8. Use of the polyarylene ether sulfone-containing particles according to any one of claims 6 and 7, or the polyarylene ether sulfone-containing particles prepared by the method according to any one of claims 1 to 5, in the preparation of coatings, films, foams, foils, membranes, or molding articles.
9. Coatings, films or foams, foils or membranes or moldings obtained using particles containing polyarylene ether sulfone according to any one of claims 6 and 7 or particles containing polyarylene ether sulfone prepared by the method according to any one of claims 1 to 5.
10. The molded article according to claim 9, wherein at least 50% of its surface area, based on the total surface area of the molded article, consists of one or more walls with a wall thickness of less than 2 mm, wherein the wall thickness can be determined according to DIN 16810 2014-7-1.
11. A method for recycling foam, foil, film, or molding material, or scraps from the preparation of coatings, foam, foil, film, or molding material according to claim 9 or 10, comprising preparing pulverized material therefrom and agglomerating it by the method according to any one of claims 1 to 5 to obtain recycled material particles.
12. The recycling method according to claim 11, wherein the scrap is agglomerated to obtain recycled particles.
Citation Information
Patent Citations
Agglomerator for thermoplastic particles has hopper around vertical drive shaft to conical funnel compressor discharge
DE102005018733A1
Process for the continuous compaction of thermoplastic plastic films and devices for carrying out this process
DE1454873A1
Process and device for the continuous fusion of thermoplastic plastic film sections to further processable granular particles
DE1454875A1
Agglomerator for continuously regranulating thermoplastic wastes, especially films, filaments and the like
EP0373372A2
Process of preparation of thermoplastic mouldings
EP0548684A1